2014
DOI: 10.3109/09513590.2014.920318
|View full text |Cite
|
Sign up to set email alerts
|

Distinct peritoneal fluid ghrelin and leptin in infertile women with endometriosis and their correlation with interleukin-6 and vascular endothelial growth factor

Abstract: The results suggest that ghrelin and leptin might play a key role in pathophysiology of endometriosis, and leptin is associated with inflammation in endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
2
13
0
1
Order By: Relevance
“…Several studies that use similar Methodology in order to observe the VEGF protein produced and not be stuck only gene expression [7,[46][47][48][49] could observe similar results to that obtained in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Several studies that use similar Methodology in order to observe the VEGF protein produced and not be stuck only gene expression [7,[46][47][48][49] could observe similar results to that obtained in this study.…”
Section: Discussionsupporting
confidence: 94%
“…Several studies have already found that the ectopic growth of endometrial-like tissue was depended upon sex steroid hormones 34 and local growth factors 35 such as insulin-like growth factor 1 (IGF-1) 36 or vascular endothelial growth factor (VEGF). 37 Commonly, short cycle length comes along with punctually ovulation and the estrogen level sharply increasing in a short period of time before ovulation. Estrogen has synergistic effects with IGF-1/VEGF and sometimes enhance the effects of IGF-1/VEGF on ectopic endometrial cells proliferation and mitosis, 38 which possibly ended with endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…Human peritoneal fluid (PF) from women with endometriosis show inconsistent protein levels of VEGF, but this may be due to sample size, dilution of PF, or true variability among women. For example, some studies show increased VEGF levels in the PF (Bourlev et al 2010, Xu et al 2013, Szubert et al 2014); however, other studies show no increase in VEGF levels in women with endometriosis compared to healthy women (Barcz et al 2012, Bersinger et al 2012, Rathore et al 2014). Interestingly, more consistency is found in animal models of endometriosis, most likely because of controlled onset of experimental conditions.…”
Section: Pathogenesis and Progression Of Endometriosismentioning
confidence: 99%